PELATIHAN KEWIRAUSAHAAN DENGAN FOKUS PEMASARAN DIGITAL: Keywords : Digital entrepreneurship, digital marketing strategies, copywriting techniques - Lati Sari Dewi Lati; Asep Saeful Falah (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
The implementation of the community service at SMK Daarul Abroor aimed to enhance students' understanding of digital entrepreneurship and the application of simple digital marketing strategies. The results showed that the participants had grasped the basic concepts of digital entrepreneurship and were able to apply digital marketing strategies effectively. The success rate of this service was measured through discussions and Q&A sessions with the participants, indicating a good understanding. To improve the effectiveness of future activities, it is recommended to provide computers with internet access to enable direct practice related to digital marketing activities. Additionally, specialized practice in copywriting techniques is also necessary to maximize digital marketing activities. This will help participants understand and apply design, content layout, and copywriting techniques more efektivitas.